Adaptations of postural sway dynamics and cortical response to unstable stance with stroboscopic vision in older adults - Tsai, Yi-Ying; Chen, Yi-Ching; Zhao, Chen-Guang; Hwang, Ing-Shiou (Frontiers in Physiology, 2022)
Background: Stroboscopic vision (SV), intermittent visual blocking, has recently been incorporated into postural training in rehabilitation. This study investigated interactions of postural fluctuation dynamics and cortical processing for the elderly during stabilometer stance with SV. Methods: Thirty-five healthy elderly maintained an upright stance on a stabilometer. Along with postural fluctuation dynamics, EEG relative power and EEG-EEG connectivity were used to contrast neuromechanical controls of stabilometer stance with SV and full-vision. Results: Compared with the full-vision, SV led to greater postural fluctuations with lower sample entropy and mean frequency (MF). SV also reduced regional power in the mid-frontal theta cluster, which was correlated to SV-dependent changes in the size of postural fluctuations. SV also enhanced the alpha band supra-threshold connectivity in the visual dorsal and frontal–occipital loops of the right hemisphere, and the supra-threshold connectivity from Fp2 positively related to variations in the MF of postural fluctuations. Conclusion: SV adds challenge to postural regulation on the stabilometer, with the increasing regularity of postural movements and fewer corrective attempts to achieve the postural goal. The elderly shift over-reliance on visual inputs for posture control with more non-visual awareness, considering deactivation of the dorsal visual stream and visual error processing.